Oral History Interview: The Bakersfield Sandstone Brick Co. Charles S. Curran interviewed by Alice Pinkerton - Curran, Charles S.; Pinkerton, Alice
Charles Curran was born in 1890 in Bakersfield, California. He was the director of Bakersfield Sandstone Brick, which was founded by his father in 1886. Curran describes the early manufacturing of sandstone brick in Bakersfield, the company's experiences during the Great Depression, World War One, and World War Two, and how the company changed from its start in early pioneer days to modern times.